The American executive and Colombian violence: Social relatedness and business ethics - Barnett, John H. (Journal of business ethics, 1991)
Three models of the response of American managers both to the violence of Colombian society and to the demands made by the Colombian narcotrafficker are identified: (1) conflict, (2) compartment, and (3) complementarity. The foundations of the models and their managerial consequences are decribed. Finally, the concepts underlying complementarity lead to social relatedness, both a new model of the business and society relationship and a guide for business ethics.